Accidental re‐exposure causing repeated severe acute generalized exanthematous pustulosis. (28th February 2019) - O'Driscoll, D.; Foria, V.; Fityan, A.; Ardern‐Jones, M.
Abstract : Click here for the corresponding questions to this CME article.